How search engines disseminate information about COVID-19 and why they should do better - Mykola Makhortykh; Aleksandra Urman; Roberto Ulloa (Harvard Kennedy School Misinformation Review, 2020)
Access to accurate and up-to-date information is essential for individual and collective decision making, especially at times of emergency. On February 26, 2020, two weeks before the World Health Organization (WHO) officially declared the COVID-19’s emergency a “pandemic,” we systematically collected and analyzed search results for the term “coronavirus” in three languages from six search engines. We found that different search engines prioritize specific categories of information sources, such as government-related websites or alternative media. We also observed that source ranking within the same search engine is subjected to randomization, which can result in unequal access to information among users.